Aicardi syndrome with type 2b interhemispheric cyst - Gowda, Vykuntaraju K.N.; Reddy, Bharath; Madivala, Bhaskar V.; Ramaswamy, Premalatha; Gowda, Sarala H.S. (Journal of Pediatric Epilepsy, 2013)
Agenesis of corpus callosum is a rare malformation of the brain. In Aicardi syndrome, it is associated with retinal lacunae and infantile spasms. Once Aicardi syndrome is diagnosed, one should look for other central nervous system malformations. We report a child who presented with developmental delay, chorioretinal lacunae and infantile spasms, due to Aicardi syndrome, associated with a type 2b interhemispheric cyst diagnosed on magnetic resonance imaging.
Keywords: Aicardi syndrome; asymmetric infantile spasms; chorioretinal colobomas; interhemispheric cyst